PENGARUH SERAT BAJA (DRAMIX) TERHADAP KUAT LENTUR PADA ROLLER COMPACTED CONCRETE (RCC) - Adita Dwi Sampurno; Iman Satyarno; Agus Taufik Mulyono (Universitas Negeri Yogyakarta, 2019)
ABSTRACTRigid pavement for highways in Indonesia started as an alternative for road pavement. Roller compacted concrete (RCC) is one type of dry concrete mixture with low water cement ratio (slump 5 cm). The RCC spreading is the same as the asphalt concrete pavement that uses the finisher and is compacted using a roller. This research uses RCC mix design with cement water factor value 0,25. Additional silicafume materials of 10%, superplasticizer 2.4%, and steel fiber (dramix) with variations of 0.5% and 1%. RCC Compaction using standard proctor tools. Testing of bending forces and compression of concrete in 1 day and 28 days. The result of research of RCC variation of 0.5% steel fiber and 1 day old concrete obtained Flexural Strength of 4,2 MPa while 28 days concrete gained Flexural Strength of 5,7 MPa. The variation of 1% steel fiber 1 day concrete obtained 3.4 MPa Flexural Strength, while the 28 days concrete obtained 6.1 MPa Flexural Strength.Keywords: Roller Compacted Concrete (RCC), Steel Fiber (dramix), Flexural Strength ABSTRAKPerkerasan kaku di Indonesia semakin banyak digunakan sebagai alternatif perkerasan jalan raya. Roller Compacted Concrete (RCC) atau beton padat giling (BPG) merupakan salah satu jenis campuran beton kering dengan faktor air semen (FAS) yang rendah (slump 5 cm). Penghamparan RCC sama seperti penghamparan perkerasan beton aspal yang menggunakan finisher dan dipadatkan menggunakan roller. Kajian ini menggunakan mix design RCC dengan nilai faktor air semen 0,25. Bahan tambah silicafume sebesar 10%, superplasticizer 2,4%, dan serat baja (dramix) dengan variasi 0,5% dan 1%. Pemadatan RCC menggunakan alat standar proctor. Pengujian kuat lentur pada beton umur 1 hari dan 28 hari. Hasil kajian RCC variasi serat baja 0,5% beton umur 1 hari diperoleh kuat lentur 4,2 MPa, sedangkan beton umur 28 hari diperoleh kuat lentur 5,7 MPa. Variasi serat baja 1% beton umur 1 hari diperoleh kuat lentur 3,4 MPa, sedangkan beton umur 28 hari diperoleh kuat lentur 6,1 MPa. Kata kunci: Roller Compacted Concrete (RCC), Beton Padat Giling (BPG), Serat baja (dramix), Kuat lentur